2022
DOI: 10.1111/pace.14542
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the over‐the‐wire microelectrodes catheter in treatment of ventricular arrhythmia arising from the left ventricular summit

Abstract: Background This study was aimed to investigate the efficacy of the over‐the‐wire (OTW) microelectrodes catheter in coronary venous system (CVS) mapping and treatment of outflow tract ventricular arrhythmia (OTVA) arising from the vicinity of the left ventricular summit (LVS). Methods Consecutive 62 patients with idiopathic OTVA in whom the OTW microelectrodes catheter was routinely used for CVS mapping were analyzed. CVS mapping was performed for both main trunk (from great cardiac vein to anterior interventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Alcohol ablation (AA) has been increasingly used as a bailout to ablation of intramural foci, especially with the increased use of epicardial and CVS activation mapping. [72][73][74] This method may be performed with ethanol delivered through a transarterial or retrograde coronary venous approach. [75][76][77] Limitations of the technique, particularly for transcoronary AA, are collateral injury to the conduction system and larger than intended infarction territory due to chemical reflux through collateral connections.…”
Section: Alcohol Ablation Therapymentioning
confidence: 99%
“…Alcohol ablation (AA) has been increasingly used as a bailout to ablation of intramural foci, especially with the increased use of epicardial and CVS activation mapping. [72][73][74] This method may be performed with ethanol delivered through a transarterial or retrograde coronary venous approach. [75][76][77] Limitations of the technique, particularly for transcoronary AA, are collateral injury to the conduction system and larger than intended infarction territory due to chemical reflux through collateral connections.…”
Section: Alcohol Ablation Therapymentioning
confidence: 99%
“…Recently, a novel over‐the‐wire 2.7‐Fr microcatheter (EPstar Fix AIV; Japan Lifeline) has become available (Figure 1). Because of its small diameter and over‐the‐wire type structure, inserting it into the CS distal veins (i.e., anterior interventricular vein or communicating vein) is feasible and can be performed safely, particularly when treating outflow tract ventricular arrhythmias 4 . Based on its high selective performance in placement into small veins, we hypothesized that inserting the microcatheter into the CS would be feasible even in patients equipped with CRT devices.…”
Section: Descriptionsmentioning
confidence: 99%
“…2,6,7 Recent studies found that the earliest activation of LVS was commonly recorded within the branch of GCV rather than the main trunk, but they did not make a distinction between the LVA vein and LVS septal veins. 8 For better recognition and understanding intuitively for electrophysiologists, we call the veins near the junction of GCV-AIV and drain towards the basal superior septum region "LV summit veins," and the veins arising from distal AIV toward the interventricular groove "septal veins.…”
Section: Patients Characteristicsmentioning
confidence: 99%